SISTEM INFORMASI GEOGRAFIS PENCEGAHAN DINI PENYEBARAN DEMAM BERDARAH DI KABUPATEN JEMBER MENGGUNAKAN METODE FUZZY - I Putu Dody Lesmana; Faiqatul Hikmah; Beni Widiawan (Jurnal Teknologi Informasi dan Terapan, 2019)
Dengue Hemorrhagic Fever (DHF) is a contagious disease that is still a public health problem. Based on the data on the number of dengue cases from 2012 to 2014, almost evenly spread of dengue fever in the district of Jember with dengue incidence rate tends to increase during the period of observation. Therefore we need a way to predict the potential spread of dengue fever in the district of Jember so it can be done early prevention. Factors - factors that affect the spread of dengue disease is rainfall (CH), the number of days of rain (HH), larva free number (ABJ), and the house index (HI) that influence vector breeding dengue disease. In this study developed a Geographic Information System using Fuzzy method to predict the spread of dengue fever by using parameters rainfall, number of rainy days, larva-free numbers, and house index in Jember. From the results of testing the potential for the spread of dengue in 31 districts of Jember district during the month of February 2014 produced 24 districts have the same comparison between the potential spread and the number of dengue cases, while 7 other districts do not correspond to the potential spread of dengue obtained accuracy of 77%.